Exploring Tourism Destination: A Potential of Mountain Tourism in Sudurpaschim Province (Journal of Tourism and Himalayan Adventures, 2023)
Exploring competitiveness of tourism destinations is very important in order to understand problems and potentials of regional tourism development and formulation of effective tourism strategies. Most of the tourists and tourism activities in Nepal are concentrated and clustered in central and north-eastern part of the country. In this context, the current paper assesses the existing status of tourism resources at provincial level and focuses on potentials and challenges in the far-western province. Three major components of tourism competitiveness as identified by Ritchie and Crouch (2003) namely, primary resources, secondary resources and tourist demand were analyzed based on 6 selected indicators and 25 variables identified by Goffi (2013). A total of 3224 sites in seven provinces were identified under core tourism resources. Core tourism is rated highest in competitiveness, while tourism policy and planning resulted a lowest rating. Bagmati has the highest score whereas Karnali has the lowest in overall competitiveness. Greater level of dispersion is found in adventure and leisure tourism resources. The study found that, though strategies like diversification and improvement of tourism products and the new area are acknowledged, specified 200 destinations under Visit Nepal 2020 don’t adhere to such standards. Visit Nepal 2020 identified the least number of touristic destination in Sudurpaschim. Though tourism infrastructure and services are found to be fair in the Sudurpaschim province, while destination promotion through digital platforms is limited. Increasing repetitive visits and seasonality are major areas of concern with the lowest rating value. It is concluded that the development and promotion of adventurous and leisure activities in Sudurpaschim have potential to diversify inbuilt seasonality of other provinces and increased length of stay. Essentially, local inhabitants should be encouraged in tourism sector, who are the immediate and most important stakeholders to proliferate the competitiveness of tourism destinations.